2021
DOI: 10.1103/physrevb.103.075116
|View full text |Cite
|
Sign up to set email alerts
|

Large twisting angles in bilayer graphene moiré quantum dot structures

Abstract: Recent exploration of the commensurate structure in the turbostratic double layer graphene shows that the large angle twisting can be treated by the decrease of the effective velocity within the energy spectra of the single layer graphene. Within our work, we use this result as a starting point, aiming towards understanding the physics of by a large angle twisted double layer graphene (i.e. Moire) quantum dot systems. We show that within this simple approach using the language of the first quantization, yet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Finally, introducing a finite twist between the two layers is a natural extension of this work which offers further degrees of tunability, both in the spatial fluctuation of mass terms due to different stackings and the different confined or edge states in the dot regions. 102,103…”
Section: Discussionmentioning
confidence: 99%
“…Finally, introducing a finite twist between the two layers is a natural extension of this work which offers further degrees of tunability, both in the spatial fluctuation of mass terms due to different stackings and the different confined or edge states in the dot regions. 102,103…”
Section: Discussionmentioning
confidence: 99%
“…Atomically thin nanomaterials provide an exciting platform for quantum technologies [1][2][3][4]. Bilayer graphene has specifically drawn great attention [5][6][7][8][9] and it was shown that bilayer graphene is a promising host for gatedefined quantum dots [10]. Quantum dots are one of the prime candidates for scalable and highly controllable quantum devices [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Polarization-dependent selection rules have been extended to TBG QDs, offering a comprehensive atlas of optical conductivity spectra and providing insights into size-scaling behavior dominated by the twist angle, enabling the manipulation of optical properties for integrated carbon optoelectronics [8]. Additionally, large-angle twisting in single-layer graphene has been investigated, emphasizing the potential of adjusting position symmetry in graphene systems [9]. Finally, the dominance of interlayer polarizability and charge transfer at small twist angles in TBG sheds light on interlayer coupling and charge transfer potential in graphene-based nanomaterials [10].…”
Section: Introductionmentioning
confidence: 99%